Analisis Ketimpangan Investasi di Wilayah Perbatasan Kalimantan Barat tahun 2015-2020 - Ulul Hidayah; Anggelina Delviana Klau; Suci Rahmawati Prima (Jurnal Ekonomi Pembangunan, 2022)
Investment is one of the essential factors in regional development because it can increase the attractiveness of a location for doing business and encourage economic growth. Increased investment is needed to encourage regional development in Indonesia, including the border area of ​​West Kalimantan. This study aims to analyze the level of inequality in development investment in the border and non-border areas of West Kalimantan and examine more deeply the level of inequality within the region and between regions in the border area of ​​West Kalimantan. The inequality analysis method used in this study is the Williamson Index and Theil Entropy Index. The analysis results show that the per capita investment inequality in non-border areas is higher than in border areas. Inequality in per capita investment in border areas is in the moderate category, but this inequality has tended to increase in the last five years. The investment disparity between the five regencies in the border area is higher when compared to the level of investment disparity between the border and non-border herd.